2010
DOI: 10.1007/s00192-010-1125-1
|View full text |Cite
|
Sign up to set email alerts
|

Intensive supervised versus unsupervised pelvic floor muscle training for the treatment of stress urinary incontinence: a randomized comparative trial

Abstract: Both intensive supervised PFMT and unsupervised PFMT are effective to treat female SUI if training session is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(126 citation statements)
references
References 20 publications
12
101
0
13
Order By: Relevance
“…Adherence was expressed as the average of series of exercises patients did monthly during the treatment period. 19 Outpatient attendance at sessions was monitored by the physiotherapist accompanying the patients during treatment and expressed as an average at the end of the three-month treatment.…”
Section: Adherence To the Pfm Training Programmentioning
confidence: 99%
“…Adherence was expressed as the average of series of exercises patients did monthly during the treatment period. 19 Outpatient attendance at sessions was monitored by the physiotherapist accompanying the patients during treatment and expressed as an average at the end of the three-month treatment.…”
Section: Adherence To the Pfm Training Programmentioning
confidence: 99%
“…Another study used the ICIQ-SF scale and demonstrated an equivalent improvement in both groups (final median in the intensive group ¼ 8 points (5 to 13) / in the home PFMT group ¼ 8 points (6 to 12); p ¼ 0.7). 24 The third study, on the other hand, demonstrated better results in the intensive PFMT group using the I-QoL scale for assessment, in which higher scores represent a better quality of life (median in the intensive group ¼ 89 points / in the home PFMT group ¼ 79 points; p ¼ 0.04).…”
Section: Home Pfmt Versus Intensive Pfmt With Physiotherapistmentioning
confidence: 91%
“…• Incontinence-specific quality of life -three studies reported this outcome, [24][25][26] but the combination of individual results through meta-analysis was not possible. One of them assessed the outcome using the Ditrovie scale (higher scores represent a worse quality of life) 25 The study estimate was not sufficiently precise to determine if intensive PFMT was more effective, less effective or no different from home PFMT.…”
Section: Home Pfmt Versus Intensive Pfmt With Physiotherapistmentioning
confidence: 99%
“…However, another study observed that after the treatment with PFME there were no differences between the two groups, and the conclusion was that the supervised PFME is not efficient to treat for stress UI if the patient in the control group is trained correctly to perform PF contraction. According to the authors, this detailed instruction before the randomization made a difference in the final result between the two groups 10 (LE 1; DR A).…”
Section: (Le 1; Dr A)mentioning
confidence: 99%
“…The approach is minimally invasive and practically has no adverse effects. Success depends on the motivation and effort both from the patient and the involved multidisciplinary team 10 .…”
Section: Introductionmentioning
confidence: 99%